The Efficacy of Continuous Venovenous Hemodiafiltration with Cytokine Filter on Sepsis - Mehtap Yıldırım; İclal Özdemir Kol; Onur Avcı; Zuhal Gülsoy; Kenan Kaygusuz; Sinan Gürsoy (Erciyes Medical Journal, 2020)
Objective: Continuous renal replacement therapy is made with high biocompatibility membranes that have high current power by using diffusion and convection together or separately. The aim of the present study was to compare the EMIC-2 and AV600S filters used for continuous venovenous hemodiafiltration (CVVHDF) with respect to the effects on sepsis, the elimination of toxins that are elevated due to acute renal injury, and the effects on inflammatory mediators in severe sepsis. Materials and Methods: The study included 38 patients who were diagnosed with severe sepsis and were treated with hemodiafiltration in the intensive care unit. Acute Physiology and Chronic Health Evaluation—2 (APACHE-2) and Sequential Organ Failure Assessment (SOFA) scores of the patients were calculated before CVVHDF starts. Hematocrit (Hct), white blood cell, blood pressure, heart rate, and body temperature values were measured and recorded. Procalcitonin (PCT), tumor necrosis factor alpha (TNF-α), interleukin (IL)-6, and IL-1 values on blood were also recorded before the process and at 8, 16, and 24 h of the process. Results: When the AV600S filtered and EMIC-2 filtered groups are compared, TNF-α values are low in the EMIC-2 filtered group (p<0.05). There is no significant difference between the groups with respect to the measurements about APACHE-2, SOFA, IL-1β, IL-6, PCT, Hct, body temperature, mean blood pressures, and heart rate. Conclusion: We think that the filters do not cause a significant change on the elimination of inflammatory cytokines, except TNF-α, on limited numbers of patients who have sepsis with acute renal injury undergoing CVVHDF with EMIC-2 and AV600S.